Intertemporal Labor Supply and Intra-Household Commitment - Pierre-André Chiappori; José Alberto Molina; J. Ignacio Gimenez-Nadal; Jorge Velilla (Institute of Labor Economics (IZA), 2019)
This paper adopts an intertemporal labor supply perspective to propose a test that allows us to distinguish between intra-household non-commitment, limited commitment, and full commitment. It investigates whether, after controling for current and future (expected) wages, past wage shocks have a lasting and significant impact on present labor supply and public consumption. Using a semi-log parametrization of labor supply and data from the Panel Study of Income Dynamics for the US, the paper shows positive evidence in favor of the limited commitment model. Specifically, unexpected past wage shocks affect labor supply in exactly the way predicted by theory, as spouses' past wage deviations have a negative impact on their labor supply and a positive impact on their spouses'. In addition, wives' past wage shocks also impact negatively household public expenditure on housing.
Keywords: D15; J22; 330; collective model; intertemporal labor supply; intra-household commitment; PSID